2013
DOI: 10.1002/hc.21109
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene‐Gallium Trichloride Complex: A Mild, Highly Efficient, and Recyclable Polymeric Lewis Acid Catalyst for Chemoselective Silylation of Alcohols and Phenols with Hexamethyldisilazane

Abstract: Polystyrene‐supported gallium trichloride (PS/GaCl3) as a highly active and reusable heterogeneous Lewis acid effectively activates hexamethyldisilazane (HMDS) for the efficient silylation of alcohols and phenols at room temperature. In this heterogeneous catalytic system, primary, secondary, and tertiary alcohols as well as phenols were converted to their corresponding trimethylsilyl ethers with short reaction times and high yields under mild reaction conditions. The heterogenized catalyst is of high reusabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In continuation of recent works on the use of polymeric catalysts in organic transformations [43,5457] and continued seeking for suitable polymer supports to immobilize catalysts on them, herein, this contribution describes in detail the use of eco-friendly suspending agents from bioresouces, guar and xanthan gums as stabilizing agents in suspension polymerization reactions, as well as their influence on the size and surface area of the synthesized polymer particles. For the purposes of this work, the synthesis of poly(St- co -DVB) cross-linked beads was chosen as the main suspension polymerization system to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of recent works on the use of polymeric catalysts in organic transformations [43,5457] and continued seeking for suitable polymer supports to immobilize catalysts on them, herein, this contribution describes in detail the use of eco-friendly suspending agents from bioresouces, guar and xanthan gums as stabilizing agents in suspension polymerization reactions, as well as their influence on the size and surface area of the synthesized polymer particles. For the purposes of this work, the synthesis of poly(St- co -DVB) cross-linked beads was chosen as the main suspension polymerization system to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Rahmatpour et al reported a catalytic and chemoselective silylation of hydroxyl group of alcohols and phenols using HMDS in the presence of polystyrenesupported gallium trichloride (PS/GaCl 3 ) as a highly active and reusable heterogeneous polymeric Lewis acid Catalyst for the activation of HMDS in dichloromethane. [125] In the mentioned research, over 29 examples of primary, secondary, and tertiary alcohols as well as phenols were studied, and their corresponding TMS ethers were obtained with short reaction times and good-to-excellent yields from 88% to 98% under mild reaction conditions, where only three substrate did not react (Scheme 32). Regarding the heterogenized catalyst, there was no need for regeneration.…”
Section: (Scheme 29) the Evolution Of Nh 3 Under These Reaction Comentioning
confidence: 99%
“…Moreover, it was highly reusable and stable in the silylation reactions and was recovered several times with negligible loss in its activity or a negligible catalyst leaching. [125] It is worth mentioning that the method can be used for chemoselective silylation of different alcohols and phenols with high yields.…”
Section: (Scheme 29) the Evolution Of Nh 3 Under These Reaction Comentioning
confidence: 99%